Tradisi Maulid Arba'in di Kampung Arab al Munawwar, Palembang - Dewi Fatonah (Jurnal Living Hadis, 2020)
This research is a qualitative descriptive study, which discusses about the tradition of the Maulid Arba’in at Al Munawwar, the Arab Villageof Palembang. The study was conducted using a living hadith approach, with the interview method as a data collection technique. To analyze the data, researcher used several stages, reducing data, describing empirial material, and then drawing conclusion and verifying them. The focus in this study is on how the Maulid Arba’in is going, the factors that influence the practice, and how the tradition of Maulid Arba’in is able to influence the community of Al Munawwar Arab Village. From this research it was found that the implementation of Maulid Arba’in which lasted for 40 days became its own uniequesness. The enthusiasm of the people is form of love to the Prophet and form of obedience as Muslims.